THE IMPACT OF MARKETING MIX (4P'S) ON CUSTOMER LOYALTY TOWARDS TOYOTA AVANZA - Rendy Harsono (iBuss Management, 2016)
With the tight competition in the automotive industry, customer loyalty has become the key for success. However, customer loyalty is not always easy to earn. With this in mind, the research is established with the goal to analyze the impact of 4P's of Marketing Mix towards customer loyalty on Toyota Avanza.Using questionnaires as data gathering instrument with simple random sampling, 124 respondents were gathered from people around Surabaya, who has bought and ride Toyota Avanza. The data obtained then analyzed using multiple linear regressions. The result shows that 4P's of Marketing Mix simultaneously has significant impact, however individually 4P's of Marketing Mix only product variable has proven to be significant toward customer loyalty. Therefore, companies, especially Toyota Astra Motor should focus on increasing the product quality of its lineup while maintaining the other factors such as price, place and promotion. Keywords: Marketing Mix (4P) , Customer Loyalty